Hubungan Peran Tenaga Kesehatan Terkait Ksehatan Reproduksi dengan Perilaku Pencegahan Seksual Pranikah pada Remaja Putri di SMKN 1 Agribisnis dan Agroteknologi Seruikabupaten Kepulauan Yapen Provinsi Papua - Lastri Tika Matui; Euvanggelia Dwilda; Budi Prasetyo (Universitas Malahayati Lampung, 2024)
ABSTRACT The transitional stage between childhood and adulthood is adolescence. The ability to reproduce is one of the physical changes that take place, yet several occurrences indicate that some teenagers lack knowledge and comprehension of reproductive health. Premarital sexual conduct is also one of the practices that endangers the health of teenagers. Teens' lack of knowledge about reproductive health is one of the things that leads them to participate in premarital sex. This study sought to ascertain the association between adolescent girls' premarital sexual conduct and the role health workers play in reproductive health at SMK Negeri Kainui. The study population consisted of all pupils at SMK N Kainui, and the research methodology employed a cross-sectional, observational analytical study design. Adolescent females enrolled in Kainui State Vocational School's classes X, XI, and XII constituting the research sample were selected completely. The study tool was a distributed questionnaire, and the Spearman's Rho test was used to process the data in order to conduct the data analysis test. Most of the 70 respondents (92.1%) answered well to the role of health workers. Most of the 69 respondents (90.8%) behaved well towards premarital sexual prevention behavior. There is a significant relationship (p=0.000) between the role of health workers and premarital sexual prevention behavior in adolescent girls. The study's conclusion indicates that adolescent girls' premarital sexual preventative activity and the involvement of health professionals are related. Keywords: Role Of Health Workers, Premarital Sexual Preventionbehavior, Adolescent Girls ABSTRAK Salah faktor yang menyebabkan remaja melakukan perilaku seksual pranikah yaitu kurangnya pendidikan tentang kesehatan reproduksi. Tujuan penelitian ini untuk mengetahui hubungan peran tenaga kesehatan terhadap kesehatan reproduksi dengan perilaku seksual pranikah pada remaja putri di SMK Negeri Kainui. Metode penelitian menggunakan desain studi analitik observasional dengan pendekatan cross-sectional dengan populasi penelitian adalah seluruh siswa di SMKN 1 Agribisnis dan Agroteknologi. Sampel penelitian adalah remaja putri di kelas XI,dan XII SMKN 1 Agribisnis dan Agroteknologi yang diambil dengan menggunakan metode total sampling. Instrumen penelitian adalah kuesioner yang disebarkan dan Uji analisis data dilakukan dengan menggunakan Uji chi square dengan mengolah data menggunakan Spss. Sebagian besar 70 responden (92,1%) menjawab baik terhadap peran tenaga Kesehatan. Sebagian besar 69 responden (90,8%) berperilaku baik terhadap perilaku pencegahan seksual pranikah. Terdapat hubungan signifikan (p=0,013) antara peran tenaga kesehatan dan perilaku pencegahan seksual pranikah pada remaja putri. Kesimpulan pada penelitian ini didapatkan hasil ada hubungan peran tenaga kesehatan dengan perilaku pencegahan seksual pranikah pada remaja putri. Kata Kunci: Peran Tenaga Kesehatan, Perilaku Seksual Pranikah, Remaja Putri